Kepastian Hukum Penerima Ganti Rugi Pengadaan Tanah: Studi Kasus Korupsi Tol Padang-Sicincin - Ruud Marino Levranda; Lexy Fatharany Kurniawan (al-Battar: Jurnal Pamungkas Hukum, 2025)
Legal Certainty Of Recipients Of Land Acquisition Compensation: A Case Study Of Padang-Sicincin Toll Corruption. Land acquisition for public interest is essential for national infrastructure development but often faces legal challenges, particularly regarding the legal certainty of compensation recipients. This study explains the compensation payment procedures based on Law Number 2 of 2012 and Presidential Regulation Number 71 of 2012, and examines the potential for criminal liability among citizens in cases of irregularities. Using a normative legal method and a case study approach on the Padang-Sicincin Toll Road corruption case, the study finds that land acquisition involves four stages: planning, preparation, implementation, and result submission. Although mechanisms are designed to ensure fairness and accountability, weaknesses in verification and supervision can be exploited for unlawful acts, such as document falsification or fictitious claims. The Amir Hosen case illustrates that citizens who knowingly commit such acts can be held criminally liable, including as perpetrators of corruption.